The role of parents in the development of faith from birth to seven years of age - Niekerk, Marsulize van (HTS teologiese studies, 2018)
Scholars have researched the role of parents in the development of the child. Families play a critical role in the development of a young child. According to Freud, many adult symptoms of anxieties are rooted in childhood experiences, and that a child’s development would influence how the child would behave as an adult and that their actions may correlate to something that occurred in their childhood. Erikson’s theory of ego development stated that the ego, which is the centre of each person’s individuality, could not be understood in isolation from the others and the wider world around it. Research has also been done on the way that a person’s faith develops. In his book, Stages of Faith, Fowler developed a theory of six stages that people go through as their faith matures. Keeley, combined his knowledge of education with his passion for children’s ministry and published a book with the title, Helping Our Children Grow In Faith. As a theology student with a background in Early childhood development, the researcher believes that these two academic areas should be utilised together to assist parents in the process of the child’s faith development during its formative years. Osmer’s core task of Practical Theology, and its four questions, will be used to determine parents’ roles in the faith development of their children. Empirical data gathered in a study by Nel and Van der Westhuizen will be used. When all four questions are answered, this study will deduce useful guidelines for parents. The importance of the role that parents play in the faith development of children is immense. A baby’s or an infant’s interaction with his or her parents forms the basis on which he or she will build their developing faith. If this foundation is not placed down correctly, problems might arise later in the child’s faith development.